(untitled) (Mathematical Proceedings of The Widya Mandira Catholic University, 2024)
This research is a qualitative study which aims to obtain an overview of high school students’ mathematical problem solving based on learning interest and self-concept on three-variable linear equation systems. This research was carried out in class X at SMAN 5 Kupang in the 2023/2024 academic year. The subjects in this research were two class Information collection in this study was carried out through the use of questionnaires, problem solving tests, and interview sessions. The data analysis process consists of three steps, namely data reduction, presenting the data, and drawing conclusions from the results. The results of this research show that subjects with high interest in learning and high self-concept are able to fulfill the four indicators of mathematical problem solving, namely the indicators of understanding the problem, making a problem solving plan, implementing the problem solving plan, and checking the answer results again. Meanwhile, subjects with low interest in learning and low self-concept only met two research indicators, namely indicators of understanding problems and making problem-solving plans. From this research, researchers provide suggestions to teachers to pay more attention to students with low interest in learning and low self-concept in understanding information in learning, especially on the ability to solve problem solving questions. For students to master the concepts and material before solving the questions given. For future researchers to add subjects of moderate ability and problem solving ability